Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/ma11020205
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Three-Dimensional Hybrid N-Doped ORR Electro-Catalysts Derived from Apricot Sap

Abstract: Rapid depletion of fossil fuel and increased energy demand has initiated a need for an alternative energy source to cater for the growing energy demand. Fuel cells are an enabling technology for the conversion of sustainable energy carriers (e.g., renewable hydrogen or bio-gas) into electrical power and heat. However, the hazardous raw materials and complicated experimental procedures used to produce electro-catalysts for the oxygen reduction reaction (ORR) in fuel cells has been a concern for the effective im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…This nding shows the crucial role played by N-doping in creating plenty of metal anchoring sites along with the tuning of the size of LDH nanostructures as well as in avoiding their agglomeration. 34,35 Furthermore, to study the need for supports for decorating discrete active LDH nanostructures, TEM analysis was extended to a support-free NiFe-LDH system. The comparative study showed that in the absence of any substrate, LDHs show more chances of agglomeration and acquiring a bulky morphology ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This nding shows the crucial role played by N-doping in creating plenty of metal anchoring sites along with the tuning of the size of LDH nanostructures as well as in avoiding their agglomeration. 34,35 Furthermore, to study the need for supports for decorating discrete active LDH nanostructures, TEM analysis was extended to a support-free NiFe-LDH system. The comparative study showed that in the absence of any substrate, LDHs show more chances of agglomeration and acquiring a bulky morphology ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there is a need for alternatives that are based on non-noble metals. Amongst the various alternatives, elements of iron triad, namely iron [1,2], cobalt [3,4] and nickel [5,6], and ntrogen-doped carbon materials [7,8], have been extensively explored as low-cost and high-performance electrocatalysts. Amongst these, iron nano-particles that are embedded in nitrogen doped conductive carbon nanostructures have aroused tremendous interest due to its excellent catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The ORR proceeds at much higher potential than the HER does and produces water, meaning that the electrical energy used to drive an electrochemical oxidation process can be saved and hazards related to hydrogen release can be avoided [ 21 ]. At present, researchers have conducted a significant amount of work on the ORR and have accumulated experience for the preparation of an efficient oxygen reducing catalyst [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%